The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jfludis.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system activity of preschool-age children who stutter

Abstract: Purpose The purpose of this study was to investigate potential differences in autonomic nervous system (ANS) activity to emotional stimuli between preschool-age children who do (CWS) and do not stutter (CWNS). Methods Participants were 20 preschool-age CWS (15 male) and 21 preschool-age CWNS (11 male). Participants were exposed to two emotion-inducing video clips (negative and positive) with neutral clips used to establish pre-and post-arousal baselines, and followed by age-appropriate speaking tasks. Respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 96 publications
3
85
1
Order By: Relevance
“…H = Hypothesis; solid arrow = significant path relations; dotted arrow = nonsignificant path relations. Buhr, et al (2014) reported that preschool-age CWS displayed a significant positive relation between parasympathetic activity indexed by respiratory sinus arrhythmia and sympathetic activity indexed by SCL. In other words, for young CWS, both parasympathetic and sympathetic activities were coactivated (i.e., higher sympathetic activity and higher parasympathetic), which is not typically expected.…”
Section: Limitationsmentioning
confidence: 96%
See 3 more Smart Citations
“…H = Hypothesis; solid arrow = significant path relations; dotted arrow = nonsignificant path relations. Buhr, et al (2014) reported that preschool-age CWS displayed a significant positive relation between parasympathetic activity indexed by respiratory sinus arrhythmia and sympathetic activity indexed by SCL. In other words, for young CWS, both parasympathetic and sympathetic activities were coactivated (i.e., higher sympathetic activity and higher parasympathetic), which is not typically expected.…”
Section: Limitationsmentioning
confidence: 96%
“…We speculate that such changes may be one possible mediator between emotional diathesis or emotional stress and stuttering. Given that sympathetic arousal has been reported to be associated with emotional diathesis (Fowles, Kochanska, & Murray, 2000;Jones, Buhr, et al, 2014) as well as emotional stress (Kreibig, 2010) and that sympathetic arousal has been studied in relation to stuttering (e.g., Adams & Moore, 1972;Ickes & Pierce, 1973;Jones, Buhr, et al, 2014;Weber & Smith, 1990), such speculation seems reasonable, and sympathetic arousal may one good candidate for a mediator. Such mediation possibly accounts for, at least in part, how emotional diathesis and/or emotional stress may be associated with stuttering.…”
Section: How Might Emotion and Stuttering Be Related?mentioning
confidence: 99%
See 2 more Smart Citations
“…Data were previously collected as part of an ongoing series of empirical investigations of linguistic and emotional associates of childhood stuttering conducted by Vanderbilt University's Developmental Stuttering Project (e.g., Arnold, Conture, Key, & Walden, 2011;Choi, Conture, Walden, Lambert, & Tumanova, 2013;Clark, Conture, Frankel, & Walden, 2012;Johnson, Walden, Conture, & Karrass, 2010;Jones et al, 2014;Millager et al, 2014;Richels et al, 2010;Walden et al, 2012). Children were paid volunteers whose caregivers learned of the study from (a) a free monthly parent magazine circulated throughout middle Tennessee, (b) a local health care provider, or (c) self-or professional referral to the Vanderbilt Bill Wilkerson Hearing and Speech Center for an evaluation.…”
Section: Participantsmentioning
confidence: 99%